Investigating HCCI Engine Operating Parameters Under the Simultaneous Dual Fueling of Ammonia and Hydrogen Based on Detailed Chemical Kinetics Modelling - Balogun, F.; Vasudev, A.; Kakoee, A.; Sirviö, K.; Mikulski, M. (Editorial de la Universitat Politècnica de València, 2024)
Challenges associated with the homogeneous charge combustion ignition (HCCI) concept includes combustion phasing control and a narrow operating window. To address the HCCI engine developmental needs, chemical kinetic solvers have been recently included in the commercial engine simulation toolchains like GT-Suite v2022. Their applicability has not been thoroughly tested, especially when less-conventional fuel options have been considered. The purpose of this study is to test the feasibility of kinetic solvers included in the GT-Suite, for simulating HCCI combustion with multi-component fuel blend, consisting predominantly of ammonia, NH3, and hydrogen, H2. The study investigated the effect of fuel blending, air to fuel equivalence ratio, and compression ratio on a dual-fuel 1-cyclinder HCCI engine model. Key combustion parameters such as peak pressure, heat release rate, start of combustion were analyzed. Feasibility of the simulations have been validated by benchmarking the results against the base-line HCCI engine fed with n-heptane (diesel surrogate). The result proved that the solver provides stable simulations for all considered fuel blends/mechanisms. Simulation times with multi-component mechanism of NH3, H2 and n-heptane are on average 32 seconds per cycle with the solver reaching convergence after 6 cycles. The optimization conducted to support the mechanism/solver feasibility study implies optimum performance can be obtained for 90% NH3 to 10% H2 blend ratio, at compression ratio of 20 with lambda value of 2. At optimal operating conditions, indicated mean effective pressure (IMEP) was almost 2.7 times higher, indicated thermal efficiency (Ieff) is few points higher, and likewise more fuel economical than the baseline HCCI operation with n-heptane. At the same time, all emission quantifiers of the NH3/H2 HCCI engine, including NOx, were significantly reduced, while keeping the intrinsic advantages of zero-carbon fuel. Finally, it was concluded that the kinetic solver posed great potentials in aiding the HCCI technological advancement, also with the use of NH3 and H2 fuel towards a zero-carbon emission transportation system.
Keywords: fi=Energiatekniikka|en=Energy Technology|